Material didáctico para la enseñanza de la Geografía desde el reconocimiento y ubicación del espacio Urbano en el grado noveno de la institución educativa Juventud del Sur, Municipio de Soacha (2022)
The following document proposes the construction of a digital didactic material, focused on the elaboration of a book on a web platform (Book Creator), with the aim of developing geographical competences in the thematic axis of recognition and location in the urban space; It is intended to implement this material with the ninth grade students of the Juventud del Sur educational institution, Soacha municipality, as part of the reinforcement exercise in parallel with the daily classes that take place in the academic weeks.